2020
DOI: 10.1101/2020.12.11.421776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The acute effects of cannabidiol on emotional processing and anxiety: a neurocognitive imaging study

Abstract: BackgroundThere is growing interest in the therapeutic potential of cannabidiol (CBD) across a range of psychiatric disorders. CBD has been found to reduce anxiety during experimentally-induced stress in anxious individuals and healthy controls. However, the mechanisms underlying the putative anxiolytic effects of CBD are unknown. We therefore sought to investigate the behavioural and neural effects of a single dose of CBD vs. placebo on a range of emotion-related measures to test cognitive-mechanistic models … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Previous reported work on this cohort (Study 1) has also shown that both strains of cannabis increase the self-report of psychotic-like symptoms (including thought and perceptual distortion, and cognitive disorganisation; Mokrysz et al, 2020 ). Subjective effects of the CBD dose in Study 2 were minimal ( Bloomfield et al, 2020b ), and no measures of psychotic-like effects were acquired. Prominent theories of schizophrenia highlight the role of (striatal) dopamine in aberrant salience attribution ( Howes and Nour, 2016 ), and this has been supported by experimental evidence from patients ( Ceaser and Barch, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reported work on this cohort (Study 1) has also shown that both strains of cannabis increase the self-report of psychotic-like symptoms (including thought and perceptual distortion, and cognitive disorganisation; Mokrysz et al, 2020 ). Subjective effects of the CBD dose in Study 2 were minimal ( Bloomfield et al, 2020b ), and no measures of psychotic-like effects were acquired. Prominent theories of schizophrenia highlight the role of (striatal) dopamine in aberrant salience attribution ( Howes and Nour, 2016 ), and this has been supported by experimental evidence from patients ( Ceaser and Barch, 2016 ).…”
Section: Discussionmentioning
confidence: 99%